Semis narration schools: systematic comparison - Al-Jubouri, Hanan; Jaber, Youssef (Al-Adab Journal, 2023)
Semiotics is charaterized by the appearance of a number of schools, each school has its own vision and position in contemporary literary criticism. These schools have branched out set of directions and approaches. The search displays the most prominent schools of sima al - sard li is the school of tarry and the Italian school and the Paris school and discuss the methodology of each school and it’s.